The Innovative Potential of the Regional System: Research, Evaluation and Management - Yu.N. STEPANOVA; S.S. MORKOVINA; D.S. PETROV; A.V. IVANOVA; S.A. KUZNETSOV (Communications of International Proceedings, 2020)
The article deals with the problem of innovative development of the regional system with an emphasis on the study of the innovative potential of economic entities, assessment of their innovative component and further management using the optimal strategy of innovative development. Using the method of assessing the innovative potential based on the process approach, representatives of various industries and economic entities were interviewed on the example of the Voronezh Region, which is part of the Central Federal District. The resulting assessment made it possible to identify the innovative potential of each economic entity using the matrix of opportunities and track its dynamics over three years. Practical conclusions of the research of innovative potential allowed to identify its key components in the regional system of assessment of innovative potential, allowed to determine the criteria of innovative susceptibility of economic entities, and management perspectives allowed to algorithmize the process of developing an innovative development strategy. The proposed methodology for assessing the innovative potential of economic entities evaluates it from the position of two components: the index of economic and technological development and the index of ability to innovate, which allows a comprehensive approach to the study of activities and the optimal development of innovative development strategies. A comprehensive assessment of the innovation potential, which forms the right management impact, leads to an increase in innovation activity and an increase in the innovation potential of economic entities of the regional system.
Keywords: Innovative Potential; Regional System; Innovative Activity; Assessment Of Innovative Potential; Strategy Of Innovative Development.